Hot corrosion behaviour of 18Cr-8Ni Austenitic Steel in presence of Na2S04 and transition metal salts - A. U., Malik; Mohammed Misbahul, Amin; Sharif, Ahmad (The Japan Institute of Metals, 2009)
Fulltext of this article is also available at http://www.journalarchive.jst.go.jp/english/jnltop_en.php?cdjournal=matertrans1960